The Global Distribution of Biological Nitrogen Fixation in Terrestrial Natural Ecosystems. Issue 3 (28th February 2020) - Davies‐Barnard, T.; Friedlingstein, P.
Abstract: Biological nitrogen fixation is a key contributor to sustaining the terrestrial carbon cycle, providing nitrogen input that plants require. However, the amount and global distribution of this fixation is highly disputed. Using a comprehensive meta‐analysis of field measurements, we make a new assessment of global biological nitrogen fixation (BNF). We assessed the relationship between BNF in natural terrestrial environments and empirical predictors of BNF commonly used in terrestrial ecosystem and earth system models. We found no evidence for any statistically significant relationship between BNF and evapotranspiration and net or gross primary terrestrial productivity. We assessed the relationship between BNF and 11 other climate variables and soil properties at a global scale. We found that all the variables we considered had little predictive power for BNF. Using averaged biome values upscaled we calculated the median global inputs of BNF in natural ecosystems as 88 Tg N year −1 . The range (52–130 Tg N year −1 ) encompasses most recent estimates and broadly agrees with recent independent top‐down estimates of BNF. The global values indicate a significant role for free living, as opposed to symbiotic, BNF, accounting for at least a third of all BNF. This work provides a new global benchmark and spatial distribution data set of BNF using a bottom‐up methodology. Key Points: Evapotranspiration and productivity (e.g., NPP) are unreliable predictors of terrestrial biological nitrogen fixation at the global scale Free‐living biological nitrogen fixation makes up at least a third of the terrestrial total Global terrestrial biological nitrogen fixation is likely in the range of 52‐130 Tg N per year